ANALYSIS OF THE INFLUENCE OF SHOPEEPAY CASHLESS E-WALLET TRANSACTIONS AND BUYING INTEREST ON CONSUMPTION BEHAVIOR ON THE MILLENIAL GENERATION IN DENPASAR CITY - I Nyoman Wahyu Widiana (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study aims to determine the effect of cashless transactions and buying interest on consumptive behavior in the Millennial Generation in Denpasar City. quantitative approach is used in completing the research results. The research data was obtained through a survey method by distributing questionnaires to 78 respondents. The results show that: (1) Cashless transactions (X1) have a significant effect on consumptive behavior, as evidenced by the t-count value of 4.348 > 1.665 and the regression coefficient of 0.390. (2) Purchase Interest (X2) has a significant effect on consumptive behavior, as evidenced by the t-count value of 6.983 > 1.665 and the regression coefficient of 0.586. (3) Cashless Transactions (X1) and Purchase Interest (X2) have a simultaneous or joint effect on consumptive behavior, as evidenced by the F-count value of 224,976 > F-table which is 3.12 with a sig value of 0.000 <0.05. (4) The magnitude of the contribution of the influence of the independent variables (X1 and x2) on the dependent variable (Y) is evidenced by the Adjusted R Square coefficient of determination of 0.853. This value indicates that the contribution or effect of cashless transactions (X1) and Purchase Interest (X2) on consumptive behavior (Y) is 85.3%. The remaining 14.7% was caused by other factors not discussed in this study.